(untitled) (World Economics and Finance Bulletin, 2025)
This study statementeffectThe extent of contribution Commercial banks in Disclosure of activities Sustainability of the same axesEnvironmental, social and economicBanking and its role in enhancing the quality of financial reports. The research followed the deductive approach in presenting the theoretical aspect and the inductive approach in presenting the practical aspect throughAnalysis of a sample of companies listed on the Iraq Stock Exchange(Ashur, Union and Gulf) Commercial Bank using sustainable disclosure standards in accordance with the topics and axes of the International Sustainability Standards CouncilISSBAnd to clarify the application of any banks to the topics of banking sustainability and its impact on enhancing the quality of financial reports by adding environmental, social and economic information, the most important conclusions were that including the topics of the Sustainability Accounting Standards Board in the reports of companies and commercial banks ensures the provision and presentation of sustainable financial reports as they disclose aspects of environmental, social and economic sustainability. The researcher used a scaleCAMPEL To indicate which indicators for each banking sustainability topic have been disclosed in a manner that achieves transparency, reliability and credibility for sustainable financial reports.